1991
DOI: 10.1128/aac.35.10.2140
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of 79 antimicrobial agents against Corynebacterium group D2

Abstract: Corynebacterium group D2 (CGD2) is involved in urinary tract infections in patients with underlying predisposing factors. This microorganism is highly resistant to a number of antimicrobial agents. We tested the activities of 79 antimicrobial agents against CGD2. (8-Lactams, aminoglycosides, and macrolides were ineffective. Fluorinated quinolones showed irregular activities, ofloxacin being the most active one. Doxycycline, rifampin, and mainly glycopeptides (vancomycin and teicoplanin) were the most active an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 10 publications
1
38
0
1
Order By: Relevance
“…Multiresistance to clinically relevant antibiotics is a prominent feature of the majority of C. urealyticum strains (García-Rodriguez et al, 1991;Funke et al, 1997). Evaluation of the complete genome sequence of C. urealyticum DSM7109 revealed the presence of an ErmX determinant encoding a 23S rRNA adenine N-6-methyltransferase (Roberts et al, 1999).…”
Section: Antibiotic Resistance Determinants Of the C Urealyticum Dsmmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiresistance to clinically relevant antibiotics is a prominent feature of the majority of C. urealyticum strains (García-Rodriguez et al, 1991;Funke et al, 1997). Evaluation of the complete genome sequence of C. urealyticum DSM7109 revealed the presence of an ErmX determinant encoding a 23S rRNA adenine N-6-methyltransferase (Roberts et al, 1999).…”
Section: Antibiotic Resistance Determinants Of the C Urealyticum Dsmmentioning
confidence: 99%
“…Encrusted cystitis may require endoscopic resectioning of encrustations and antibiotic therapy for permanent cure (Funke et al, 1997;van Hooland et al, 2005). The majority of C. urealyticum strains are, however, highly resistant to a large number of antibiotics, including ␤-lactams, aminoglycosides, and macrolides (García-Rodriguez et al, 1991;Soriano et al, 1995;Martínez-Martínez et al, 1998), although the glycopeptides vancomycin and teicoplanin remain universally active against these isolates (Soriano et al, 1991(Soriano et al, , 1998Lagrou et al, 1998). It has been suggested that the appearance of multiresistant C. urealyticum strains is favored by the use of antibiotics in hospital settings and that these strains are likely to be acquired by inpatients directly from the bacterial flora present in the hospital environment (Garcia-Bravo et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Considering these values, an initial report (6) showed that all strains of C. jeikeium were susceptible to CIP, but a more recent study (9) showed that only 36% of C. jeikeium strains were susceptible to this fluoroquinolone. Similarly, initial data concerning C. urealyticum (10) showed that all strains tested were susceptible to OFL; in a later report (2) …”
mentioning
confidence: 99%
“…It is critical that studies of the activities of antimicrobial agents be based on testing microorganisms identified according to the new taxonomic criteria, in order to really obtain clinically significant information and to allow the comparison of data obtained from different laboratories (3,5,13,19,24). Unfortunately, there is yet no standardized methodology for susceptibility testing of coryneform bacteria.…”
mentioning
confidence: 99%
“…only the category of susceptibility to ampicillin and penicillin has been suggested (16). There is scant information on the activities of antimicrobial agents against coryneform bacteria (4)(5)(6)9). C. jeikeium, C. urealyticum, and C. amycolatum are usually multiresistant organisms, and only glycopeptides remain universally active against these species (4-6, 18, 19, 22, 23).…”
mentioning
confidence: 99%